Assessing the geochemical fingerprint of the 2010 Eyjafjallajökull tephra through instrumental neutron activation analysis: a trace element approach - Baccolo G.; Clemenza M.; Delmonte B.; Maffezzoli N.; Nastasi M.; Previtali E.; Maggi V. (Journal of Radioanalytical and Nuclear Chemistry, 2015)
The first characterization by INAA of the tephra erupted during the most explosive phase of the 2010 Eyjafjallajökull (Iceland) eruption is here presented. To evaluate the homogeneity of the tephra and fragmentation processes not only bulk samples were considered, but also other grain size fractions and previously published data. Concentrations of 42 elements were determined. Specific attention was given to incompatible elements, which appeared to be the most significative in order to define a geochemical fingerprint of the event.